Nutraceutical Food: Composition, Biosynthesis, Therapeutic Properties, and Applications - do Prado, Débora Z. [UNESP]; Capoville, Bruna L. [UNESP]; Delgado, Clarissa H.O. [UNESP]; Heliodoro, Julia C.A. [UNESP]; Pivetta, Mayara R. [UNESP]; Pereira, Milene S. [UNESP]; Zanutto, Mirella R. [UNESP]; Novelli, Paula K. [UNESP]; Francisco, Valesca C.B. [UNESP]; Fleuri, Luciana F. [UNESP] (Elsevier, 2018)
Diseases, such as cardiovascular system problems, diabetes, obesity, and cancer are frequent in last decades due to poor eating habits and sedentary lifestyle, mainly in industrialized countries where population consumes diets with extra calories and nutrients imbalance. Consumption of therapeutic food is a viable alternative to reverse this situation as they have specific characteristics that contribute to the prevention and treatment of diseases due to the presence of bioactive compounds. The action of these compounds to reduce the risk of diseases is directly related to the bioactivity of metabolites, such as polyunsaturated fatty acids, triglycerides, steroids, flavonoids, isoflavones, carotenoids, vitamin C, and other antioxidants. In general, they are present in low concentrations in food, consequently they have low bioactivity when compared to pharmaceuticals products; however, once they are ingested regularly as part of the diet, they may present long-term noticeable physiological effect. These bioactive compounds are the subject of recent studies and further research to elucidate its effects and benefits are extremely important. Thus, this chapter aims to address the major consumed and currently studied nutraceutical foods, its compositions, biosynthesis, therapeutic properties, and applications, as well as discussions of its acceptance by the population, validation by the scientific community, and regulatory directive.
Keywords: Antioxidants; Hormone analogs; Polyunsaturated fatty acids; Probiotics; Thermogenic